Investigation of Antioxidant and Antimicrobial Properties of Sunda Porcupine’s (Hystrix javanica, F.Cuvier 1823) Quills Ethanolic Crude Extract - Muhamad Arif Budiman,; Pamungkas Rizki Ferdian,; Tri Hadi Handayani,; Rizki Rabeca Elfirta,; Masrukhin,; Herjuno Ari Nugroho,; Ni Luh Putu Rischa Phadmachanty,; Wartika Rosa Farida,; Ardya Widyastuti,; Dianita Dwi Sugiartanti, (Tropical Life Sciences Research, 2024)
The Sunda porcupine (Hystrix javanica, F.Cuvier, 1823) is a rodent-mammal species native to Indonesia and is utilised in traditional medicine for the treatment of various ailments. Some ethnic communities in Indonesia have traditional beliefs regarding Sunda porcupine’s quills, which are thought to relieve back pain and toothache. Despite this traditional knowledge, there is limited scientific research on the topic. The aim of this study was to identify active compound in an ethanolic crude extract of Sunda porcupine’s quills, and to evaluate its antioxidant and antimicrobial properties. The antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH)-free radical scavenging assay while the antimicrobial activity was evaluated through microdilution resazurin assay. The total phenolic and flavonoid contents were also determined to support the antioxidant properties. The active compounds were identified using gas chromatography-mass spectrophotometer (GCMS) with the National Institute of Standards and Technology (NIST-11) library. The result showed that the extract possesses antioxidant properties (IC50 138.93 ?g/mL) and antimicrobial properties against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Bacillus subtilis (B. subtilis), Pseudomonas aeruginosa (P. aeruginosa) and Candida albicans (C. albicans) (IC50 range 0.40 mg/mL–33.05 mg/mL). Total phenolic content (TPC) and total flavonoid content (TFC) were 27.29 ± 2.20 mgGAE/g and 27.09 ± 1.66 mgQE/g, respectively. A total of 24 active compounds from the crude extract were identified. As much as five compounds serve as antioxidant agents, including: butylated hydroxytoluene; eicosane; 1-iodo-hexadecane; methyl ester hexadecanoic acid; and L-(+)-ascorbic acid 2,6-dihexadecanoate. Furthermore, as much as 11 compounds serve as antimicrobial agents, including: tetradecane; pentadecane; 2-isopropyl-5-methyl-1-heptanol; hexadecane; butylated hydroxytoluene; eicosane; 1-iodo-hexadecane; methyl ester hexadecanoic acid; benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, methyl ester; L-(+)-ascorbic acid 2,6-dihexadecanoate; and octadecanoic acid. This study provides scientific validation for the use of the Sunda porcupine’s quills in traditional medicine and highlights the potential for further research in animal bioprospecting.